A VIEW OF MICHEL FOUCAULT’S CONCEPTS OF POWER AND SUBJECT: SURVELLIANCE SOCIETY (Third Sector Social Economic Review, 2018)
The starting point of this study is the Foucauldian’s conceptualization of the relation between power and subject as n factual acceptance in anywhere and any situtation. According to Foucault, subject, which gets obeyed by the politics of disciplinary and regulatory whitin the society, is different than the agent. This study appraches how the subject is constructed, what are the differences from the agent and how the power works for constructing the subject. Therefore, this study aims at analyzing the reconstruction of the “subjectified” agent, which sees itself as a free will, spirally by the power. The Foucauldian approach embodies that analyze as a problematization and questioning process, and points the reconstruction of the agent from the subject questioned the power. Foucault emphasizes the role of the intellectual in that revolution. It is executed how the subject is rescued from survelliance society by intellectual. Hence, in this study it is revealed how the relationship of the power, the subject and the agent work with by Foucauldian perspective.
Keywords: Power; Agent; Subject; Problematization; Revolution; Survelliance Society